Association between opioid use and readmission following liver transplantation. Issue 10 (24th August 2016) - Rogal, Shari; Mankaney, Gautham; Udawatta, Viyan; Good, Chester B.; Chinman, Matthew; Zickmund, Susan; Bielefeldt, Klaus; Jonassaint, Naudia; Jazwinski, Alison; Shaikh, Obaid; Hughes, Christopher; Humar, Abhinav; et al.
Abstract: The aim of this study was to assess the independent association between pre‐transplant prescription opioid use and readmission following liver transplantation. We reviewed the medical records of all patients at a single medical center undergoing primary, single‐organ, liver transplantation from 2004 to 2014. We assessed factors associated with hospital readmission 30 days and 1 year after hospital discharge using multivariable competing risk regression models. Among 1056 transplant recipients, 49 (4.6%) were prescribed pre‐transplant prescription opioids. Readmission occurred in 421 (40%) patients within 30 days and 689 (65%) within 1 year. Patients with pre‐transplant opioid use had a significantly higher risk of readmission at 30 days (HR 1.7; 95% CI 1.1–2.5) and a non‐significantly elevated risk at 1 year (HR 1.4; 95% CI 1.0–1.9) when controlling for other potential confounders. Although pain was the major reason for readmission in only 12 (3%) patients at 30 days and 33 (6%) patients at 1 year, pre‐transplant opioid use was significantly associated with pain‐related readmission at both time points. In conclusion, prescription opioid use pre‐transplantation was significantly associated with all‐cause 30‐day readmissions and pain‐related readmissions at 30 days and 1 year.